Creative drama in higher education: effects on students’ communication skills - Cam Turkan, Cigdem (Frontiers in Education, 2025)
In this study, which employed creative drama as a teaching method, was carried out with the participation of 36 first-year students enrolled in the elective course Communication Skills in the Department of Nutrition and Dietetics during the fall semester of the 2024–2025 academic year. A mixed-methods design was employed in the study. In the quantitative dimension, a single-group experimental design without a control group was used, while the qualitative data were collected through interviews. The analysis techniques applied to the dependent and independent variables in the study were: A t-test for dependent samples, a t-test for independent samples, and an ANOVA analysis. Qualitative data obtained from the interview questions posed at the end of the study were analyzed. Students’ responses were coded, and similar codes were aggregated to form themes. The findings were presented in tables and figures. At the end of the study, it was observed that the students developed greater awareness of communication, acquired strategies for resolving conflicts, and showed improvements in personal attributes such as self-confidence, self-awareness, and self-expression. Throughout the process, the students were energetic, actively engaged in the activities, and eager to participate in the lessons. The activities contributed to the enhancement of their communication skills, self-confidence, and social interactions. Additionally, students reported that they demonstrated increased respect for others’ opinions and made efforts to behave more impartially.